Tailoring the structure and electrochemical performance of sodium titanate anodes by post-synthesis heating. Issue 47 (9th November 2022) - Yin, Wei; Barim, Gözde; Peng, Xinxing; Kedzie, Elyse A.; Scott, Mary C.; McCloskey, Bryan D.; Doeff, Marca M.
Abstract : A simple post-synthesis heating approach tailors the crystal structure, surface chemistry, and electrochemical properties of sodium titanate anode. Abstract : Sodium titanate anodes synthesized via "chimie-douce" methods generally require a post-synthesis dehydration step. Their crystal structures are sensitive to the heating conditions such as temperature, resulting in distinct sodium storage performance. Herein, using in situ and ex situ high-temperature X-ray diffraction, we studied in detail the structural changes of Na0.74 Ti1.815 □0.185 O4 ·1.27H2 O (NTO) under various heating conditions. Electrochemical characterization revealed that NTOs heated at lower temperatures with layered structures deliver larger capacities than those heated at high temperatures with tunnel structures. Heat treatment at moderate temperatures greatly improves the capacity retention of NTO, especially stabilizing the high voltage processes that are major contributors to the capacity fading, because of the modified crystal structure and surface chemistry. Our findings suggest that post-synthesis heating is a simple and effective strategy to tailor the crystal structure, surface chemistry, and electrochemical properties of sodium titanate anodes.